Numerical approximation of Blasius equation using Daftardar-Gejji and Jafari method / Mat Salim Selamat ... [et al.] - Selamat, Mat Salim; Ramli, Siti Maisarah; Rasuli, Rafika; Mohamad, Nadia (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In this study, the Blasius equation is solved by using the Daftardar-Gejji and Jafari method (DJM)(Daftardar-Gejji and Jafari, 2006). The Blasius equation is a third order nonlinear differential equation which comes from boundary layer equations. The obtained series solution is combined with the diagonal Pad´e approximants to handle the boundary condition at infinity. DJM was applied to compute approximate solutions for Blasius equation. The computation verify that the DJM is an effective tool for solving nonlinear problem in fluid dynamic. Combination with Pad´e approximants provides a promosing tool to handle problems on an unbounded domain.